2022
DOI: 10.1093/g3journal/jkac018
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Drosophila lines for LexA-dependent gene and growth regulation

Abstract: Conditional expression of short hairpin RNAs (shRNAs) with binary genetic systems is an indispensable tool for studying gene function. Addressing mechanisms underlying cell-cell communication in vivo benefits from simultaneous use of two independent gene expression systems. To complement the abundance of existing Gal4/UAS-based resources in Drosophila, we and others have developed LexA/LexAop-based genetic tools. Here, we describe experimental and pedagogical advances that promote the efficient conversion of D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 26 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…Compared to kinase regulators of insulin signaling [1, 6] phosphatases remain relatively understudied. Drosophila genetic screens have revealed phosphatases governing wing disc circadian systems, and embryonic development [12, 24-26]. In a genetic screen of Ser/Thr phosphatases, we found that Pp1-87B suppression potently inhibited Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Compared to kinase regulators of insulin signaling [1, 6] phosphatases remain relatively understudied. Drosophila genetic screens have revealed phosphatases governing wing disc circadian systems, and embryonic development [12, 24-26]. In a genetic screen of Ser/Thr phosphatases, we found that Pp1-87B suppression potently inhibited Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings suggested the pAktHF ELISA could be used to identify novel genetic regulators of insulin resistance, an established risk for type 2 diabetes [5]. To investigate this possibility, we first assessed pAktHF changes in flies after genetic suppression of known insulin signaling regulators ( Figure 4A ; [12]). After shRNA knockdown in fat body of the insulin receptor ( InR ) or chico , the Drosophila ortholog of IRS1/2, we observed a significant reduction of pAktHF in ad libitum fed flies ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior studies, we produced and characterized novel fly enhancer trap lines through an interscholastic partnership of secondary school and university-based researchers in the U.S. (Kockel et al 2016, 2019; Chang et al 2022). This involved development of curricula permitting flexible scheduling of laboratory-based ‘modules’: in some schools, this occurred in year-long courses ( Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…There were also multiple positive outcomes for students and teachers at partnering schools that were unanticipated. These included (1) emergence of student course alumni as instructors at their home institution or another Stan-X partner site (n = 6), (2) interscholastic collaboration and data development through sharing of Stan-X fly strains and other resources, (3) regular video conferencing and in-person multi-institutional student symposia organized independently by Stan-X instructors, (4) additional professional development opportunities for adult teachers, including presentation of pedagogy at professional meetings, promotion, and travel to other Stan-X partner schools, (5) development of new courses founded on CRISPR and other approaches to generate novel LexA or LexAop strains (Chang et al 2022; Wendler et al 2021) or fly genomics (see Kockel et al 2019), (6) development of Stan-X summer school courses at Harvard, Oxford, Lawrenceville and Exeter ( Suppl. Figure 1B , https://stan-x.org), and (7) philanthropic funding for science curricular innovation and infrastructure modification to Stan-X partners.…”
Section: Resultsmentioning
confidence: 99%